Association of Clinical Severity With Family Affluence–Based Socioeconomic Status Among Hospitalized Pediatric Hand, Foot, and Mouth Disease Patients in Henan, China: A Single Hospital-Based Case Series Study. (26th March 2021) - Wang, Kai; Wang, Fang; Li, Yu; Liang, Lu; Cui, Peng; Han, Shujuan; Zhou, Yonghong; Qiu, Qi; Cheng, Yibing; Guo, Chun; Zeng, Mengyao; Long, Lu; et al.
Abstract: Background: The association between the clinical severity of hand, foot, and mouth disease (HFMD) inpatients and socioeconomic status (SES) is important for quantifying SES inequality in HFMD disease burden and informing decision-makers regarding medical subsidy and reimbursement policies. Here, this association was investigated using a quantitative SES measurement. Methods: Laboratory-confirmed HFMD cases hospitalized at Henan Children's Hospital from February 15, 2017, to February 15, 2018, were invited. We utilized the revised Family Affluence Scale for family affluence–based SES measurement. Clinical severity was diagnosed based on central nervous system (CNS) complications, treatments, and length of stay. We applied logistic regression for association analyses and multiple imputation for missing data. Results: A total of 1229 laboratory-confirmed HFMD inpatients responded. Adjusted by age, sex, rural residence, EV-A71 infection, and health-seeking behavior, CNS complications (odds ratio [OR], 2.72; 95% CI, 1.41–5.31), intensive care unit (ICU) admission (OR, 7.30; 95% CI, 2.21–25.97), and prolonged hospitalization (OR, 4.28; 95% CI, 2.44–7.58) were significantly associated with lower family affluence–based SES. These associations increased as the SES category descended. For EV-A71-infected inpatients, severe HFMD was significantly associated with low and intermediate SES. For non-EV-A71-infected inpatients, only the association of prolonged hospitalization with low SES increased significantly. Also, severe HFMD inpatients, especially those admitted to the ICU, incurred high hospitalization costs. Conclusions: The clinical severity of HMFD inpatients was significantly associated with family affluence–based SES. Severe HFMD inpatients were more likely to have lower SES than nonsevere inpatients and suffered a heavy economic burden. Therefore, medical subsidy and reimbursement policies should offer sufficient monetary support to severe HFMD inpatients to alleviate economic burden in low-SES populations and reduce potential SES inequality.